2020
DOI: 10.2147/dddt.s277160
|View full text |Cite
|
Sign up to set email alerts
|

<p>Cinnamaldehyde Inhibits the Function of Osteosarcoma by Suppressing the Wnt/β-Catenin and PI3K/Akt Signaling Pathways</p>

Abstract: Background Osteosarcoma (OS) is a primary bone tumor associated with locally aggressive growth and early metastatic potential that typically occurs in children and adolescents. Chinese traditional medicine Cinnamomum cassia Presl has been shown to have significant tumor-killing effect, in which cinnamaldehyde (CA) is the main active ingredient. Purpose To explore the anticancer effect of CA on the osteosarcoma cells and the possible molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 39 publications
(41 reference statements)
3
20
0
Order By: Relevance
“… Liu et al (2020) used GeneCards and OMIM databases for the enrichment analysis and found that CA is closely related to the AKT/PI3K signaling pathway in breast cancer. Liu and Huang confirmed that CA regulated colorectal cancer and osteosarcoma progressing via the AKT/PI3K signaling pathway ( Li et al, 2016 ; Huang et al, 2020 ). In our present study, Western blotting results showed that CA was able to downregulate the phosphorylation levels of PI3K/AKT pathway proteins in A2780 and SKOV3 cells with or without EGF.…”
Section: Discussionmentioning
confidence: 89%
“… Liu et al (2020) used GeneCards and OMIM databases for the enrichment analysis and found that CA is closely related to the AKT/PI3K signaling pathway in breast cancer. Liu and Huang confirmed that CA regulated colorectal cancer and osteosarcoma progressing via the AKT/PI3K signaling pathway ( Li et al, 2016 ; Huang et al, 2020 ). In our present study, Western blotting results showed that CA was able to downregulate the phosphorylation levels of PI3K/AKT pathway proteins in A2780 and SKOV3 cells with or without EGF.…”
Section: Discussionmentioning
confidence: 89%
“…Study has showed that L-arginine affects the metabolic tness and viability of T cells which were critical for anti-tumor responses (Geiger et al 2016). Cinnamaldehyde inhibits proliferation, migration, invasion and promotes apoptosis of OS cells and is a potentially valid antitumor agent (Huang et al 2020). 4-Allyl-2-methoxyphenol inhibits non-small cell lung cancer by inhibiting NF-B to regulate TRIM59 expression (Cui et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…80 Cinnamaldehyde promotes the cell apoptosis and inhibits the cell proliferation, migration and invasion in OS cells via inhibiting the Wnt/β‐catenin pathway. 81 MiR‐1236‐3p inhibits the progression of OS via targeting Wnt3a 3’ UTR. 82 Similarly, in this study, the Wnt/β‐catenin pathway was also inhibited by melatonin.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the Wnt/βcatenin pathway increases the chemoresistance of OS cells 80. Cinnamaldehyde promotes the cell apoptosis and inhibits the cell proliferation, migration and invasion in OS cells via inhibiting the Wnt/β-catenin pathway 81. MiR-1236-3p inhibits the progression of OS via targeting Wnt3a 3' UTR 82.…”
mentioning
confidence: 99%